A new correlation between global solar energy radiation and daily temperature variations. (June 2015) - Dumas, Antonio; Andrisani, Andrea; Bonnici, Maurizio; Graditi, Giorgio; Leanza, Gianni; Madonia, Mauro; Trancossi, Michele
Highlights: The energy balance for an atmospheric layer near the soil is evaluated. A new atmospheric parameter F, called action of temperature variation, is defined. A linear relationships between the global daily solar energy and F is stated. We tested this relationships with data from 7 sites of the Mediterranean area. The results show a comparable accuracy with other well-known solar energy models. Abstract: The energy balance for an atmospheric layer near the soil is evaluated. By integrating it over the whole day period, a linear relationship between the global daily solar radiation on a horizontal surface and the product of the sunshine hours at clear sky with the daily maximum temperature variation is achieved. The results for the monthly averaged daily values show a comparable accuracy with some well recognized models such as the Ångström–Prescott one, at least for Mediterranean climatic area. Validation of the results has been performed using old data sets which are almost contemporary and relative to the same sites with the ones used for the comparison.